The Impact of Conceptual Art On Contemporary Saudi Arabian Islamic And American Ceramics In Light Of The Concept Of Globalization - Al-Shimare, M. Shaimaa Ali Flaieh Mazban (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2024)
The current research dealt with the study (The impact of conceptual art on contemporary Saudi Arabian and American ceramics in light of the concept of globalization). The researcher relied on the descriptive (analytical) method by describing and analyzing samples from the research to achieve the research objective. This was done to search for indicators derived from the theoretical framework as benchmarks in analyzing the research sample. The result reached by the researcher is that globalization has generally dominated art, including contemporary ceramics, which has influenced the form and content of artistic production and the use of different techniques and methods in artistic production. In the context of globalization, an artwork is considered incomplete without the presence of the audience. The results of contemporary globalized art emphasized individuality and personal freedom in artistic production, whether related to form, content, or technique, to achieve self-uniqueness and to emphasize the individual's personality in society